2000
DOI: 10.1111/j.1471-0528.2000.tb10403.x
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting fetal weight distribution in women with type I diabetes

Abstract: Objective To identify factors independently affecting fetal weight in women with type I diabetes.Design Prospectively recorded data in consecutive women with type I diabetes, between 1975-1 992. Setting Simpson Memorial Maternity Hospital, Edinburgh.Population Three hundred and two pregnancies with type I diabetes identified before pregnancy, with antenatal care and delivery in the Simpson Memorial Maternity Hospital, a singleton pregnancy, and the same diabetic physician.Methods Normal ranges for birthweight … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
36
0

Year Published

2000
2000
2010
2010

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(42 citation statements)
references
References 24 publications
6
36
0
Order By: Relevance
“…As previously reported [26], this effect was partially related to metabolic control during pregnancy. Our data and previous data on much fewer subjects [27] indicate that metabolic control as measured by HbA 1c during the final trimester is an important contributor to the increased birthweight in children of mothers with diabetes. The mechanism of this phenomenon is not completely understood, but elevated levels of fetal insulin, leptin and lipids are potentially responsible [28].…”
Section: Discussionsupporting
confidence: 70%
“…As previously reported [26], this effect was partially related to metabolic control during pregnancy. Our data and previous data on much fewer subjects [27] indicate that metabolic control as measured by HbA 1c during the final trimester is an important contributor to the increased birthweight in children of mothers with diabetes. The mechanism of this phenomenon is not completely understood, but elevated levels of fetal insulin, leptin and lipids are potentially responsible [28].…”
Section: Discussionsupporting
confidence: 70%
“…It has proved difficult to establish a clear relationship between HbA 1 c levels and infant birthweight. Positive [18,20] and negative [19,21] correlations have been reported between first trimester HbA 1 c levels and infant birthweight, while other studies have shown that third trimester HbA 1 c levels are positively related to infant birthweight [1,2]. A constant finding of these studies is that the relationship between HbA 1 c levels and infant birthweight is weak.…”
Section: Introductionmentioning
confidence: 97%
“…However, even in patients with near-normal HbA 1 c levels, macrosomia rates remain high [2,4,5]. Several studies on the relationship between HbA 1 c levels and birthweight have been published [15][16][17][18][19]. It has proved difficult to establish a clear relationship between HbA 1 c levels and infant birthweight.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hyperglycaemia is considered a determinant of excessive foetal growth, although the relationship between glycaemic control during pregnancy and the occurrence of macrosomia is lower than might be expected. Differences in HbA 1c explained only 6 to 23% of the variance in birth weight [5,11,12], whereas 1 h postprandial blood glucose values predicted 28.5% of the macrosomic infants born to diabetic mothers [13]. This relatively weak relationship could be due to the use of inadequate markers of (overall) glycaemic control or due to other yet unknown factors.…”
mentioning
confidence: 99%